1989
DOI: 10.3133/ofr89261
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic injection, storage, and withdrawal of heated water in a sandstone aquifer at St. Paul, Minnesota: Field observations, preliminary model analysis, and aquifer thermal efficiency

Abstract: This second model was calibrated with data from an 8-day ambient-temperature injection test at 18.9 L/s. Boundary-flux conditions were examined for nonisothermal conditions by simulating 8 days of injection of 150 °C water at 18.9 L/s. Results of simulations using both models indicate that the flux-boundary conditions are adequate for simulations of short-term heat-injection testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…An aquifer test at the ATES site was used to determine that the transmissivity of the Ironton and Galesville Sandstones was approximately 690 ft 2 /d, and the storage coefficient was approximately 2.4 x 10 -5 (Miller and Delin, 1993, p. A8-A9). The vertical-to-horizontal hydraulic conductivity ratio for the Ironton and Galesville Sandstones was determined by Miller and Delin (1993) to be 0.1.…”
Section: Previous Hydraulic Investigationsmentioning
confidence: 99%
“…An aquifer test at the ATES site was used to determine that the transmissivity of the Ironton and Galesville Sandstones was approximately 690 ft 2 /d, and the storage coefficient was approximately 2.4 x 10 -5 (Miller and Delin, 1993, p. A8-A9). The vertical-to-horizontal hydraulic conductivity ratio for the Ironton and Galesville Sandstones was determined by Miller and Delin (1993) to be 0.1.…”
Section: Previous Hydraulic Investigationsmentioning
confidence: 99%
“…Miller and Voss (1986) described the design of the finite-difference grid at the ATES site. Miller and Delin (1993) described (1) analysis of field observations for aquifer characterization and observation-network design, (2) preliminary model analysis to determine model sensitivity to hydraulic and thermal characteristics and to facilitate final model design, and (3) model simulations of the aquifer's thermal efficiency. Miller and De lin ( 1994) described analysis of the thermal data and nonisothermal modeling for the short-term test cycles.…”
Section: Introductionmentioning
confidence: 99%
“…However, few documented case studies other than permit applications are available in which the Basic Plume Method was used to simulate injected waste movement. In reports by Miller andothers (1986a, 1986b), who are the principal writers of the method code, the method was used to simulate the effects of injection for an injection practice in Texas. The results of using the method indicated that the estimated extent of horizontal migration was in close agreement with an estimation based on using a threedimensional numerical method.…”
Section: Layer Dispersion Characteristics -Dispersion In the Basicmentioning
confidence: 99%
“…Related articles by Merritt include "Recovering Fresh Water Stored in Saline Limestone Aquifers" (Merritt, 1986); "A Review of Factors Affecting Recovery of Freshwater Stored in Saline Aquifers" (Merritt, 1988); and "Nonunique Simulations of the Quality of Water Recovered Following Injection of Freshwater into a Brackish Aquifer" (Merritt, 1991). In addition, the Intercomp model was used in a study by Miller (1989) to evaluate cyclic injection, storage, and withdrawal of heated water in a sandstone aquifer at St. Paul, Minn.…”
Section: Model Summary and Case Studies -Thementioning
confidence: 99%